Critical Review of Recent Papers in Learning Media: Advantages, Challenges, and Future Prospects - Gunarso, Gunarso; Wahyudin, Wahyudin; Ranggana, Alfaza; Permatasari, Endah; Aprianto, Vani; Septiani, Hesti (Journal of Education Research, 2024)
With the rapid development of technology at this time, the use of learning media is very necessary to support an interesting learning process and can motivate students to participate in learning. The aim of this research is to critically review the use of learning media, including the advantages of the media itself, the challenges faced and the prospects for using learning media in the future. The research method used is bibliometric analysis, utilizing machine learning to map data. This research consists of four stages of bibliometric analysis, namely: data collection using the Publish or Perish application, data processing, data mapping using machine learning, and mapping data analysis using the R programming language. Journal which is a reference published between two thousand nineteen and two thousand twenty three from the Google Scholar database. The search process uses the keyword learning media. The research results show that bibliometric analysis and mapping of 1000 publications using machine learning allows a deeper understanding of developments, trends and important aspects of research in the field of learning media. By using a bibliometric analysis approach and applying machine learning, this research contributes to the development of the use of technology in implementing learning media.